2015
DOI: 10.1104/pp.15.00026
|View full text |Cite
|
Sign up to set email alerts
|

Site-Specific Nitrosoproteomic Identification of EndogenouslyS-Nitrosylated Proteins in Arabidopsis

Abstract: Nitric oxide (NO) regulates multiple developmental events and stress responses in plants. A major biologically active species of NO is S-nitrosoglutathione (GSNO), which is irreversibly degraded by GSNO reductase (GSNOR). The major physiological effect of NO is protein S-nitrosylation, a redox-based posttranslational modification mechanism by covalently linking an NO molecule to a cysteine thiol. However, little is known about the mechanisms of S-nitrosylation-regulated signaling, partly due to limited S-nitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
172
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 208 publications
(200 citation statements)
references
References 77 publications
12
172
0
1
Order By: Relevance
“…We reasoned that the NO-enhanced APX1 enzymatic activity might be partly attributed to S-nitrosylation. Consistent with this notion, APX1 was identified as a putative S-nitrosylated protein by nitrosoproteomic studies (Fares et al, 2011;Hu et al, 2015). By using the biotin-switch method (Jaffrey and Snyder, 2001), we found that APX1 recombinant protein was efficiently S-nitrosylated in vitro ( Fig.…”
Section: Apx1 Is a Positive Regulator Of No-modulated Resistance To Osupporting
confidence: 72%
See 1 more Smart Citation
“…We reasoned that the NO-enhanced APX1 enzymatic activity might be partly attributed to S-nitrosylation. Consistent with this notion, APX1 was identified as a putative S-nitrosylated protein by nitrosoproteomic studies (Fares et al, 2011;Hu et al, 2015). By using the biotin-switch method (Jaffrey and Snyder, 2001), we found that APX1 recombinant protein was efficiently S-nitrosylated in vitro ( Fig.…”
Section: Apx1 Is a Positive Regulator Of No-modulated Resistance To Osupporting
confidence: 72%
“…S6). Moreover, this residue has also been identified to be S-nitrosylated in Arabidopsis by proteomics studies and in pea by a mass spectrometric study, respectively (Fares et al, 2011;Begara-Morales et al, 2014;Hu et al, 2015). The importance of Cys-32 is evident by the observation that soybean APX1 contains a single Cys residue (accession no.…”
Section: Discussionmentioning
confidence: 97%
“…A large number of proteins regulating a range of metabolic and developmental processes are known to be targets of NO (Hu et al, 2015). Assuming that the observed shift is related to hyperaccumulation of NO in shr mutant, it is plausible that it may have affected the activity of several key proteins regulating cellular metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…ABA‐induced NO can modify the reactive cysteine thiol in a protein to form S‐nitrosothiol. Protein S‐nitrosylation is important for protein activity and stability (Hu et al ). OST1 activity is abolished by S‐nitrosylation at cysteine (Cys) 137, which is adjacent to the kinase catalytic site (Wang et al ), suggesting that NO regulates ABA signaling via a feedback circuit.…”
Section: Apoplastic H2o2 Mediates Stomatal Movement During Aba Signalingmentioning
confidence: 99%